Pelatihan Peduli Dukun Bayi Sebagai Agen Promotor Air Susu Ibu Eksklusif pada Ibu Hamil - Martha, Evi; Normala, Shinta (Universitas Ahmad Dahlan, 2017)
Background: Promotions of exclusive breastfeeding during the first six months of a childâs life have been made throughout the world, including Indonesia. Exclusive breastfeeding movement in Indonesia specifically supported through Government Regulation Number 33 of 2012. Unfortunately, the report shows that the proportion of exclusive breastfeeding EBF) is low. Government regulation is not the only way to reach successful EBF practice, while other people supports are also needed. Traditional Birth Attendants (TBA) are the people closest to the mothers especially in rural areas. The role and potency of traditional birth attendants can be used to promote exclusive breastfeeding on the mother. Method: Therefore training program was held involving 55 TBAs as participants at Ciampea District, Bogor Regency to support and improve exclusive breastfeeding practices in this area. Furthermore, to determine the effectiveness of the provision of material for the training is done using the method of cross-sectional studies. Training activities and the measurement were conducted in May and October 2013. Result: The result showed that the training was able to provide new knowledge about exclusive breastfeeding at TBAs. Conclusion: Furthermore, after all the training, there was increase in knowledge, attitude and practice of Exclusive breastfeeding promotion by TBAs. Knowledge increased two times, attitude 1.5 times, and practice two times.